Anti‐human serum albumin autoantibody may be involved in the pathogenesis of autoimmune bullous skin diseases. Issue 6 (5th May 2020) - Qian, Hua; Cao, Yan; Sun, Junfeng; Zu, Jianing; Ma, Liang; Zhou, Haizhou; Tang, Xianling; Li, Yan; Yu, Haiyang; Zhang, Mingyu; Bai, Yunlong; Xu, Chaoqian; et al.
Abstract: Although effective immunological diagnostic systems for autoimmune bullous skin diseases (AIBD) have been established, there are still unidentified cutaneous autoantigens. The purpose of this study is to investigative whether anti‐human serum albumin (HSA) autoantibodies exist in AIBD sera and their potential pathogenesis. By immunoprecipitation‐immunoblotting, immunofluorescence assay, anti‐HSA autoantibodies could be detected in AIBD sera; by ELISAs, positive rates of AIBD sera for IgG and IgA anti‐HSA autoantibodies were 29% and 34%, respectively. The IgG anti‐HSA autoantibodies in ABID sera recognized a number of HSA antigen epitopes and therefore a polyclonal antibody against HSA were next employed to study its pathogenesis. In vitro cell and tissue culture models, anti‐HSA antibody could influence DNA damage‐related signaling proteins, via activation of phospho‐p38 signaling pathway. This is the first report that an autoantibody may influence DNA damage‐related signaling proteins. Statistical analyses also proved that anti‐HSA autoantibodies were positively correlated with various known autoantibodies and clinical features of ABID patients. In summary, IgG and IgA autoantibodies to HSA may have diagnosis values for AIBD. DNA damage‐related signaling proteins might be involved in the pathogenic role of anti‐HSA autoantibodies in AIBD. Phospho‐p38 signaling pathway is a potential target for treatment of AIBD positive for serum anti‐HSA autoantibodies.